Comparing English Premier League goalkeepers: Identifying the pitch actions that differentiate the best from the rest - Oberstone, J. (Journal of Quantitative Analysis in Sports, 2010)
The Opta Index is a prestigious performance measure used to assess English Premier League (EPL) football players. Although the Opta model is proprietary, the general structure uses a multiattribute collection of subjectively weighted pitch measures that either rewards or penalizes a player with a potential range of points based on the quality of his game performance. In addition, the specific set of measures used depends upon player position: forwards, midfielders, defenders, and goalkeepers each have their own unique set of measures even though there might be some overlap. Although the player's Opta Index is calculated for each game, it is the cumulative "grade card"—the final Opta Index calculated at the end of the thirty-eight game EPL season in May—that is of particular importance. The index, along with the large array of player pitch data, is commercially distributed to the EPL clubs and appears in a wide variety of television and print media outlets. This paper proposes an alternative to using the full set of Opta data by identifying those specific pitch actions that form a statistically significant retrodictive linear regression model for the 2007-2008 EPL season. Additionally, the importance of evaluating pitch actions historically assumed to be clearly pertinent measures—such as goals allowed per game for the goalkeeper—will be not only be appraised from a statistical viewpoint, but also from a practical perspective.